Characterizing the structure of protein-protein interaction networks - Zea, Allan A; Rueda-Toicen, Antonio (arXiv.org, 2016)
Network theorists have developed methods to characterize the complex interactions in natural phenomena. The structure of the network of interactions between proteins is important in the field of proteomics, and has been subject to intensive research in recent years, as scientists have become increasingly capable and interested in describing the underlying structure of interactions in both normal and pathological biological processes. In this paper, we survey the graph-theoretic characterization of protein-protein interaction networks (PINs) in terms of structural features, and discuss its possible applications in biomedical research. We also perform a brief revision of network theory's classical literature and discuss modern statistical and computational techniques to describe the structure of PINs